New Keynesian Phillips Curve for Pakistan (The Pakistan Development Review, 2007)
Recently macroeconomists have moved to a new neo-classical synthesis by integrating Keynesian features like imperfect competition and nominal rigidities with dynamic stochastic general equilibrium model of the Real Business Cycle Theory with micro foundations and rational expectations, [see, for instance, McCallum and Nelson (1999)]. The standard model comprises of a trinity; consumption and inflation adjustment equations with a monetary authority’s reaction function. One of the pillar of the modelinflation adjustment equation, also known as New Keynesian Phillips Curve (NKPC) in the literature, has at least two important features; unlike the traditional Phillips curve the NKPC is forward-looking; and it has been derived from the profit maximising behaviour of the firms in a monopolistically competitive market structure.